Training For The Development Of Extensive Materials In The Digital Era As A Solution To Fisheries Extension Activities With Digital Submitting Of Information - Lubis, Ahmad Fauzan; Diana, Ayu; Fikri, Muhammad Zakiyul; Syahputra, Andri (Andalasian International Journal of Social and Entrepreneurial Development, 2021)
Background: snacks or fast food are currently favored by children's and even dominate the foodmarket. This food has penetrated all regions and its development very fast from day to day. This increase inconsumption of snacks is not followed by an increase in the nutritional value in them and most of the snacksas children's snacks that are currently circulating contain many substances that are harmful to health, such asdyes, preservatives and excessive MSG. This cannot be allowed to continue because it also affects theintelligence of children. This requires a media as the delivery of information to the public as a whole. One ofthe media that can convey information globally is information that is connected to the internet network,especially in streaming videos on social media channels. In order to raise awareness of the Indonesianpeople, especially the people of Tanjungbalai about the benefits and advantages of eating fish, so Departmentof Fish Processing Technology Polytechnic Tanjungbalai (TPHP POLTAN) carries out training activities forthe creation of extension materials in the digital era. The desired result of this activity is that students cancreate counseling materials through video media, blogs/vlogs that are presented online. Method : The formof this activity consists of providing material and making video demos. The materials provided in thisactivity are: 1) Fish Product Diversification, 2) Processed Product Quality Management and 3) Video makingand editing tutorials. Result : the training process in making video demos of making products from fisheryproducts as a form of counseling material for the community to be able to make their own snacks that aremore nutritious and have a delicious taste. The stages in this training are as follows: 1) Participants makevideo material to be made, 2) Shoot or record videos according to the material, and 3) Participants do videoediting to get a good video.